Radiological and biomechanical evaluation of rabbit tibia with critical-sized defect treated with Malaysian made osteopaste in comparison with commercially available bone cements - Wan Maihan binti Wan Salleh (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Critical size bone defect (CSD) is a defect that will not heal spontaneously over a period of time. Gold standard treatment for CSD is bone graft to promote healing and regeneration. However, the use of bone graft is associated with several complications such as prolonged hospitalization, infection, bleeding and persistent pain. Synthetic bone graft substitutes have been introduced to overcome these limitations. Previously, histological evaluation and radiograph imaging had been used to assess the healing process of bone. However, these tests are insufficient to assess the functional mechanical properties of the healing bone. The objective of this study was to evaluate biomechanical properties of bone defect treated with Osteopaste (a local product) in comparison with JectOS and MIIG®X3 (commercialized products). New Zealand White rabbits were divided into four groups: control group (Sham operation, n=3); JectOS treatment (n=12); MIIG®X3 treatment (n=12) and Osteopaste treatment (n=12). Each group was further divided into four rabbits for each duration with sham group one rabbit for each duration. CSD was created at the right proximal tibia of the rabbits and the defects were filled with the biomaterial as assigned. The rabbits were euthanized after 6 weeks, 12 weeks and 24 weeks duration. Ex vivo imaging using micro-CT Skyscan was done to assess bone healing followed by compression test by using Instron machine where stress-strain curve was generated to represent the mechanical properties of bone. Statistical analysis was done between different biomaterial groups using one-way ANOVA. P < 0.05 was taken to be statistically significant. Ex-vivo imaging showed JectOS material persistently present in the defect over duration with minimal defect closure. MIIG®X3 showed complete resorption over duration with minimal bone healing. Osteopaste showed partial resorption of biomaterial and new bone formation with minimal bone defect closure over duration. The only parameter with significant difference is the energy at maximum load between Osteopaste group and JectOS group and Osteopaste group and MIIG®X3 group at 6 weeks. There was no significant difference of other biomechanical parameters between different biomaterial groups. In conclusion, local product Osteopaste is as effective as JectOS and MIIG®X3 (commercialized products) as substitutes biomaterial for the treatment of bone defect.